2015
DOI: 10.1111/bij.12659
|View full text |Cite
|
Sign up to set email alerts
|

Investigating thermal acclimation effects before and after a cold shock inDrosophila melanogasterusing behavioural assays

Abstract: Acclimation to environmental change can impose both costs and benefits to organisms. In this study we explored to what extent locomotor behaviour of Drosophila melanogaster is influenced by developmental temperature and adult temperature in both the laboratory and the field. Following development at 15, 25, or 31 °C, adult flies were tested for locomotor activity at all developmental temperatures in the laboratory before and after exposure to a cold shock and in the field for their ability to locate resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…In a recent study, we showed that an increase in heat tolerance in response to heat hardening of O. cincta under laboratory conditions is associated with lowered cold tolerance (Alemu et al, ). However, it has been argued that cost and benefit of thermal plasticity under laboratory conditions might not be ecologically relevant and are context dependent (Bahrndorff, Gertsen, Pertoldi, & Kristensen, ; Kristensen et al, ). In addition, the temperature regimes simulated under laboratory conditions may not reflect the variation and predictability of the temperature changes that could happen under natural conditions, and where other biological and environmental parameters are varying as well (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we showed that an increase in heat tolerance in response to heat hardening of O. cincta under laboratory conditions is associated with lowered cold tolerance (Alemu et al, ). However, it has been argued that cost and benefit of thermal plasticity under laboratory conditions might not be ecologically relevant and are context dependent (Bahrndorff, Gertsen, Pertoldi, & Kristensen, ; Kristensen et al, ). In addition, the temperature regimes simulated under laboratory conditions may not reflect the variation and predictability of the temperature changes that could happen under natural conditions, and where other biological and environmental parameters are varying as well (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we find evidence that there may be critical developmental windows where cold temperatures can change an aspect of the adult phenotype. These data might explain why the conclusions of field recapture studies can deviate from conclusions of laboratory activity studies (Kristensen et al ., ; Bahrndorff et al ., ). Moreover, the present study highlights the importance of measuring traits with different thermal sensitivities.…”
Section: Discussionmentioning
confidence: 97%
“…We do see a shift in activity with long‐term exposure, although this shift is in the vertical position of the performance curve, such that long‐term exposure to both heat and cold results in reduced activity across all six temperatures. Although this is somewhat unexpected for stimulated movement, it is in accordance with other studies looking at spontaneous movement using DAMs, where flies that develop at intermediate temperatures show higher behavioural activity across test temperatures (Zamudio et al ., ; Gilbert, ; Kjærsgaard et al ., ; Bahrndorff et al ., ). One possible explanation for the lower activity could be that we measure locomotor activity as spontaneous movement and animals that develop at temperatures above or below optimum may be more likely to conserve their energy.…”
Section: Discussionmentioning
confidence: 99%
“…An increased negative geotaxis behaviour, i.e. the flies crawled higher, was interpreted as beneficial, because the ability to escape a potential stressful environment is of key importance for fitness66.…”
Section: Methodsmentioning
confidence: 99%